On Aqueducts and Anxiety: Water Infrastructure, Ruination, and a Region-Scaled Anthropocene Imaginary. Issue 1 (2nd January 2022) - Randle, Sayd
Abstract : This paper explores popular expectations for and meanings of the U.S. West's environmental future, as articulated through recent artistic representations of the Los Angeles's expansive water provision network. Weaving together material from participant observation and readings of creative works, I show how infrastructural imagery is used to index anxieties about a future of water scarcity. Presenting familiar, currently functional water infrastructures as ruins-in-the-making, these artists use the physical stuff of water provision networks to advance critiques of longstanding modes of development and the material basis of urban-rural relations in the U.S. West. Doing so, these imagined ruins draw the global-scale threat of climate change into a protracted regional story of landscape-making (and ruining). These works suggest the potential power of such a meso-scale approach to the Anthropocene concept for orienting empirical scholarship, enabling analysts to explore how global processes and local histories co-produce regional imaginaries and landscapes alike.